Experimental study of flash boiling spray with isooctane, hexane, ethanol and their binary mixtures. (15th May 2021) - Yan, Junhao; Gao, Suya; Liu, Wenchuan; Chen, Tairan; Lee, Timothy H.; Lee, Chia-Fon
Highlights: The spray flash boiling of three component fuels (isooctane, hexane, and ethanol) were studied. Adding ethanol or hexane to isooctane both promote flash boiling. Droplet size continuously decreased as the percentage of hexane increased. Spray collapse for all fuels occurred when the pressure ratio of ambient to saturation pressure dropped below 0.3. Abstract: The main objective of this study is to understand the effect of fuel properties on flash boiling sprays using multi-hole injectors. Macroscopic characteristics were investigated using Diffused Backlight Imaging (DBI) and quantified with liquid penetration length and spray angles. Phase Doppler Anemometry (PDA) was applied to measure the droplet size and velocity. Behaviors of spray with three single-component fuels (isooctane, hexane, ethanol) under different ambient pressures (100 kPa, 80 kPa, 50 kPa, 22 kPa) as well as their binary mixtures under different blend ratios (10%, 30%, 85%) were reported and analyzed. The results showed that adding ethanol or hexane to isooctane could both promote flash boiling by increasing the overall vapor pressure thus superheated degree. Under mixing ratios of 10% and 30%, sprays with ethanol blends showed more severe flash boiling comparing with sprays with hexane blends. Shorter liquid penetration and better liquid dispersion have been observed. Comparing with isooctane spray, the droplet size continuously decreased with increasing hexane content due to enhanced breakup and faster vaporization. Sprays with ethanol mixtures showed a different trend. Noticeable droplet size reduction has been observed for spray with 10% ethanol content. However, droplet size did not further decrease with higher blend ratios regardless of higher flash boiling intensity. Such observations indicate severe vaporization inhibition caused by the high latent heat of vaporization of ethanol. For sprays with all test fuels, collapsing occurred when the pressure ratio of ambient pressure to saturation pressure ( Rp ) dropped below 0.3.